Analisis Skeptisme Professional Auditor, Etika Profesi, Keahlian Auditor dan Pengalaman Auditor Terhadap Pemberian Opini Auditor (Study pada Badan Pengawasan Keuangan dan Pembangunan) - Arisang, Irdianty; Yusuf, Marwah; Faisol, Faisol (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This research was conducted with the aim of testing the effect of auditor professional skepticism, professional ethics, auditor expertise, and auditor experience on the accuracy of giving auditor opinions. The population of this study was the auditor who worked at the South Sulawesi Provincial Representative Office of BPKP, amounting to 87 people and taking the data by questionnaire. Multivariate regression analysis was applied with the help of the STATA 14 application, which was preceded by a validity test, a reliability test, and a classic assumption test. The results of this study indicate that: (1) professional auditor skepticism has a significant effect on the accuracy of giving auditor opinion (2) professional ethics has a significant effect on the accuracy of auditor opinion (3) Expertise has no significant effect on the accuracy of giving auditor opinion (4) Experience has significant effect on accuracy of auditor's opinion.